Wastewater Treatment with Geotextile Filters: The Role in Permeability and Pollutant Control - Maria Vitoria Morais; Leonardo Marchiori; Josivaldo Sátiro; Antonio Albuquerque; Victor Cavaleiro (Applied Sciences)
The application of geotextiles as filter materials in various systems, such as biofilters, wetlands, and wastewater treatment plants, has grown significantly in recent years. The ability of these materials to support biofilm growth makes them ideal for the removal of organic and inorganic contaminants present in wastewater. The objective of this research was to analyze clogging through variations in permeability, using column tests for 80 days with two types of nonwoven geotextiles with different grammages (GT120 and GT300), as well as to study the efficiency in the removal of organic matter. A synthetic wastewater was used, allowing the specific observation of biological clogging and the treatment carried out exclusively by microorganisms. The results indicated that bioclogging was not a significant factor within the experimental period. Through the mass test, a continuous increase in biofilm growth over time was observed for both geotextiles. For scanning electron microscopic (SEM) images, GT300 presented a larger biofilm area. A higher removal of COD (80%), N (52%), and P (36%) by microorganisms present in GT300 was found, which appears to be associated with its greater thickness and weight. The higher mesh density provides a larger area for the growth of microorganisms, allowing a greater amount of biomass to establish itself and contributing to the efficient removal of pollutants. These findings highlight the potential of using geotextile filters in wastewater treatment applications, where biofilm growth can positively contribute to contaminant removal without immediately compromising permeability.